Blood Cells and Venous Thromboembolism Risk: A Two-Sample Mendelian Randomization Study - He, Jiahao; Jiang, Qian; Yao, Yiting; Shen, Yi; Li, Juan; Yang, Jianuo; Ma, Ran; Zhang, Nuofu; Liu, Chunli (Frontiers in Cardiovascular Medicine, 2022)
Background: Previous studies have shown that various cell indices are associated with a higher risk of venous thromboembolism (VTE), however whether these findings reflect a causal relationship remains unclear. Therefore, we performed a two-sample Mendelian randomization (MR) analysis to assess the causal association of various blood cells with VTE risk. Study Design and Methods: Summary statistics of genetic instruments representing cell indices for erythrocytes, leukocytes, and platelets were extracted from genome-wide association studies of European ancestry, by Two-Sample Mendelian Randomization. Inverse variance weighting (IVW) was used as the primary analytical method for MR. Sensitivity analyses were performed to detect horizontal pleiotropy and heterogeneity. Results: Genetically predicted red blood cell distribution width, mean reticulocyte volume, and mean red blood cell volume were positively associated with VTE, with odds ratio (OR) of 1.002 (CI 1.000 - 1.003, P=0.022), 1.003 (CI 1.001-1.004, P=0.001, respectively) ) and 1.001 (CI 1.000-1.002, P=0.005). Genetically peroxided monocyte count was negatively correlated with VTE, with OR=0.998 (CI 0.996-0.999, P=0.041). Conclusion: Genetically liability to high- red blood cell distribution width, mean reticulocyte volume, mean red blood cell volume, and low monocyte count are associated with the higher risk of VTE.